A meta‐analysis of climate change effects on forage quality in grasslands: specificities of mountain and Mediterranean areas. (22nd March 2015) - Dumont, B.; Andueza, D.; Niderkorn, V.; Lüscher, A.; Porqueddu, C.; Picon‐Cochard, C.
Abstract Atmospheric carbon dioxide (CO2), global mean temperature and interannual variability in temperature and rainfall are expected to increase significantly by the end of the 21st century. To review the effects of these factors on forage quality, we carried out a meta‐analysis of climate manipulation experiments. The first notable result was a lack of effect of elevated CO2 on structural carbohydrates and digestibility. Elevated CO2 increased the total non‐structural carbohydrates of forage tissues by an average of 25% and decreased forage nitrogen (N) content by 8%. Increased legume abundance in multispecies swards can, however, maintain N concentration in the harvested biomass. There were no consistent effects of warming on contents of N, water‐soluble and structural carbohydrates, or on digestibility. We highlight the continuum in the effect of water availability, from drought to irrigation, with a curvilinear increase of forage N as water availability decreased. Digestibility increased, on average, by 7% with drought, but with strong experimental variations. The review places special emphasis on discussion of the specificities of mountain and Mediterranean grasslands, the former being limited by low temperature, the latter by drought and heat. Elevated CO2 decreased forage N content in mountain areas and in temperate plains alike. It increased N content by an average of 3% in Mediterranean areas; this could be due to shifts in vegetation communities under elevated CO2 or to a greater concentration of N in plant tissues under drought conditions. Further experiments are needed to investigate the effects of combined factors, including extreme climatic events.